Logika Kebijakan Kurikulum Berbasis Cinta: Analisis Instrumen Negara dan Kapasitas Preventif terhadap Radikalisasi dalam Pendidikan Madrasah - Atikah Putri Dinanty (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the policy logic of the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC), formalized through the Minister of Religious Affairs Decree Number 1503 of 2025, as a state instrument for preventing radicalization in Indonesian madrasahs. Studies exploring the relationship between policy instruments, the construction of religious moderation, and radicalization processes within curriculum design remain relatively limited. This research employs a qualitative library research approach based on policy document analysis by integrating Christopher Hood’s NATO framework, William F. Pinar’s Curriculum as Political Text perspective through Norman Fairclough’s Critical Discourse Analysis, and Quintan Wiktorowicz’s theory of radicalization processes. The findings indicate that KBC represents a partially coherent policy package, with its strongest dimensions lying in nodality and authority, while gaps remain within the treasure dimension. The Panca Cinta structure also demonstrates conceptual links to stages of radicalization, particularly religious seeking and frame alignment, through dialogical, reflective, and interdisciplinary learning approaches. This study argues that KBC functions not merely as an administrative curriculum, but also as a preventive policy design for strengthening religious moderation in madrasah education